Design of mobile application for SME business sustainability during post Covid-19 - Zainuddin, Ahmad Anwar; Ahmad Puzi, Asmarani; Sahak, Rohilah; Abdul Rahman, Siti Husna; Abdul Majid, Mohamed Ibrahim; Jusat, Nuaomi; Mohd Mansor, Ahmad Fairuzabadi; Hamizan, Hasbullah; Subramaniam, Krishnan; Svpk, Satya Devu; Mohamad Yunos, Muhammad Farhan Affendi (Institute of Electrical and Electronics Engineers Inc. (IEEE), 2022)
— In the 21st century, mobile and portable devices have become an integral part of people's lives, assisting them in managing daily tasks, whether for work or personal reasons. Furthermore, this technology will benefit people, particularly those who run small to medium-sized businesses (SMEs), by allowing them to manage their firms’ using smartphones and other portable devices from anywhere and at any time. However, many SMEs in Malaysia do not own a mobile app. During this Covid-19 pandemic, the country's economic growth rate has slowed. It has impacted negatively on all types of businesses on a massive scale. Several major retailers have temporarily closed their doors. Aside from that, poor footfalls are causing problems for medium and small-sized enterprises. They have entirely lost their businesses due to the absence of a mobile app. They might still earn profits if they had their smartphone app because the delivery sectors were still operating as usual. The primary purpose of this study is to create importance of using electronic commerce mobile applications among SME business owners. This ecommerce mobile application was developed using Android studio with Kotlin programming language. UI of this application was designed with simple widget and layout. Google Firebase platform was connected to Android studio application which is used to store user details and verify whenever user try to login